The crimson flame - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories, 1983)
The Hardy brothers travel to an Arizona ranch and eventually, Thailand in pursuit of jewel thieves who have stolen a priceless ruby.